Microcomb-based integrated photonic processing unit - Bowen Bai; Qipeng Yang; Haowen Shu; Lin Chang; Fenghe Yang; Bitao Shen; Zihan Tao; Jing Wang; Shaofu Xu; Weiqiang Xie; Weiwen Zou; Weiwei Hu; et al. (Nature Communications, 2023)
Optical neural networks face remarkable challenges in high-level integration and on-chip operation. In this work the authors enable optical convolution utilizing time-wavelength plane stretching approach on a microcomb-driven chip-based photonic processing unit.